Higher Education in Maine: A Conversation with Sally Vamvakias - Vamvakias, Sally (Maine Policy Review, 2000)
This conversation between Sally Vamvakias, former chair of the University of Maine System Board of Trustees took place on October 5, 1999. At the time, Vamvakias had just completed her ten-year tenure as a trustee, the last four as chair. In this forward-looking conversation, Vamvakias talks about the change that electronic forms of knowledge transmission are bringing to higher education, and lays out the challenges to the University of Maine System as we begin the new millennium. This interview was conducted for Maine Policy Review by Luisa S. Deprez of the University of Southern Maine.
Keywords: Maine higher education; University of Maine System